Comparison of apatinib and capecitabine (Xeloda) with capecitabine (Xeloda) in advanced triple-negative breast cancer as third-line therapy: A retrospective study - Li, Yi-Hui (Medicine (Baltimore), 2018)
The treatment of advanced triple-negative breast cancer, which failed in first-line or second-line therapy, is a significant challenge. We conducted this retrospective study to explore the efficacy and safety of apatinib and capecitabine as the third-line treatment for advanced triple-negative breast cancer. This retrospective study involved 44 advanced triple-negative breast cancer patients who failed in first-line or second-line therapy in Tangshan People's Hospital from January 2016 to February 2017. Twenty-two patients received apatinib and capecitabine, while 22 patients were treated with capecitabine monotherapy as third-line therapy. The progression-free survival (PFS), objective response rate (ORR), disease control rate (DCR), and adverse events were compared between 2 groups. The apatinib and capecitabine group exhibited a higher PFS than capecitabine group (P = .001). Meanwhile, ORR and DCR in apatinib and capecitabine group were better than in capecitabine group (P = .042; .016). The 2 groups showed no significant difference in adverse events except degree I-II bleeding (P = .021). Both the apatinib and capecitabine and the capecitabine regimens revealed good tolerability. The apatinib and capecitabine regimen can achieve a better efficacy and similar serious adverse events compared with capecitabine regimen as the third-line treatment for advanced triple-negative breast cancer.